2010
DOI: 10.1186/1471-2407-10-272
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity during Cancer Treatment (PACT) Study: design of a randomised clinical trial

Abstract: BackgroundFatigue is a major problem of cancer patients. Thirty percent of cancer survivors report serious fatigue three years after finishing treatment. There is evidence that physical exercise during cancer treatment reduces fatigue. This may also lead to an improvement of quality of life. Such findings may result in a decrease of healthcare related expenditures and societal costs due to sick leave. However, no studies are known that investigated these hypotheses. Therefore, the primary aim of our study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 28 publications
(35 reference statements)
2
36
0
5
Order By: Relevance
“…Indeed, our study found a relatively high percentage of trials with unclear blinding status, varying between 48.5% (for blinding of patients) and 84.1% (for blinding of data analysts) [1]. At the same time, it has been previously documented, and confirmed in our study, that a substantive percentage of trials not reporting the blinding status of those involved had actually blinded them [2].…”
Section: Conservative Handling Of Missing Informationsupporting
confidence: 70%
See 1 more Smart Citation
“…Indeed, our study found a relatively high percentage of trials with unclear blinding status, varying between 48.5% (for blinding of patients) and 84.1% (for blinding of data analysts) [1]. At the same time, it has been previously documented, and confirmed in our study, that a substantive percentage of trials not reporting the blinding status of those involved had actually blinded them [2].…”
Section: Conservative Handling Of Missing Informationsupporting
confidence: 70%
“…As noted by Berger [2], ''in most cases the parties with the most vested interests in the outcomes are the very ones conducting the studies, and enjoying the discretion to sway the results one way or another. The last thing we want, from a scientific perspective, is to provide incentives to these experimenters to 'accidentally' lose some key data.''…”
Section: Conservative Handling Of Missing Informationmentioning
confidence: 98%
“…We will discuss several alternatives using the PACT study as an example [1]. The PACT study is a multicenter randomized controlled trial (RCT) that studies the (cost) effectiveness of exercise during cancer treatment.…”
Section: The Problemmentioning
confidence: 99%
“…Participants who were allocated to the control group were recommended to be physically active for at least 30 minutes a day, 5 days a week according to the Dutch guideline for physical activity [14], which is based on international recommendations [15,16]. During the pilot study, 64 patients were included (September 2008eDecember 2009) [1]. The proposed Zelen design could have been effective if patients had not had the chance to meet each other.…”
Section: Pilot Study Using the Zelen Design With Consent To Postponedmentioning
confidence: 99%
“…Estos resultados coinciden con lo descrito por Velthuis et al 41 , quienes observaron que una intervención con entrenamiento de resistencia durante 18 semanas reducía de manera significativa los niveles de fatiga en pacientes con cáncer de mama y cáncer de colon en fase de tratamiento activo. De manera similar, Winters-Stone et al 42 concluyen que el entrenamiento de resistencia no sólo reduce la fatiga en pacientes oncológi-cos, sino que además disminuye la posibilidad de sufrir caídas accidentales en estos pacientes.…”
Section: Figuraunclassified